High voltage direct current transmission : converters, systems and DC grids - Jovcic, Dragan (John Wiley & Sons, 2020)
"The book describes HVDC (High Voltage Direct Current) Transmission technologies including LCC (Line Commutated Converter) HVDC, VSC (Voltage Source Converter) HVDC and the latest VSC HVDC based on MMC (modular multilevel converters), as well as the principles of building DC transmission grids. When the first edition was written, the MMC converters were just being introduced, but nowadays they have become standard HVDC technology. In the second edition many updates will be made and several new chapters/sections will be introduced, particularly, the latest MMC converters will be covered in more depth. Also, DC switchgear and DC grid protection will be expanded following the latest developments on the market and in research projects"-- Provided by publisher
Keywords: Electric power distribution -- Direct current.; Electric power distribution -- High tension.; Electric current converters.; elektronické knihy; electronic books